Identification of Early Mobilization Interventions in Cardiovascular Disease Patients in Hospital - Gala, Merry; Syam, Yuliana; Tahir, Takdir (JOSING: Journal of Nursing and Health, 2023)
This study aims to categorize various early mobilization therapies in heart disease patients. The research method used is a systematic review by searching for articles using the Science Direct, PubMed, and Google Scholar databases. Key phrases included "early mobilization," "exercise training," and "cardiovascular disease and heart failure." The results showed that the interventions had 6MWT, CPET, progressive mobilization I, muscle breathing/inhalation training on day I, leg and limb exercises on the second and third days, ambulation, limb exercises, sitting, and walking. Around the bed, low-intensity resistance exercises in bed, and standing and tiptoe exercises on the floor beside the bed. Patients with acute heart failure often receive 20 to 40 minutes of therapy daily, including bedside exercises and a 50-step walk. In conclusion, there are still differences in time, scope, and implementation of early mobilization initiatives. However, mobilization therapy can be given to cardiac patients of all ages and is safe and practical. They help reduce re-hospitalization risk and improve a patient's VO2 and quality of life (QOL). Keywords: Heart Failure, Exercise, Early Mobilization, Exercise, Cardiovascular Disease